Penerapan Metode Support Vector Machine (SVM) untuk Memprediksi Pemilihan Karir bagi Alumni UMSIDA - Qur'ani, Meisyilia Difanada; Setiawan, Hamzah; Kautsar, Irwan Alnarus (STKIP PGRI Tulungagung, 2025)
The success of a university is not only determined by its educational process but also by the ability of its graduates to get a job. The aim of this research is to develop and evaluate a predictive model using the Support Vector Machine (SVM) method to predict career choices for alumni of the Muhammadiyah University of Sidoarjo (UMSIDA) . This research uses a quantitative approach, in the topic of predicting sample data obtained from tracer data of Umsida students which is compiled into the title